THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FOSTERING VIRTUOUS CHARACTER AMONG STUDENTS IN TAKALAR REGENCY - Imel Putri Dewita; Muh. Nur Fithri D; Abubakar Abubakar; Nurqadriani Nurqadriani (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in fostering students’ noble character (akhlakul karimah) in secondary schools in Takalar Regency. The research focuses on identifying teaching strategies, forms of exemplary conduct, and challenges faced by teachers in developing students’ moral character. A descriptive qualitative approach was employed, using in-depth interviews, participatory observation, and open-ended questionnaires as data collection techniques. The research subjects consisted of PAI teachers, school principals, and several students selected purposively. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that PAI teachers play a crucial role as educators, moral mentors, and role models for students. Core Islamic values such as honesty, responsibility, discipline, and politeness are instilled through habituation, exemplary behavior, and contextual learning. The supportive school environment and parental involvement further reinforce students’ moral formation. However, teachers also face challenges such as the negative influence of digital media, limited time for moral instruction, and insufficient coordination between schools and families. The study concludes that the success of moral education depends significantly on teachers’ exemplary conduct and the collaborative efforts of all stakeholders. It is recommended that PAI teachers continue to develop adaptive, example-based teaching methods, while schools and parents strengthen cooperation to create a conducive educational environment for nurturing students’ Islamic character and moral integrity.